Analisis Normalisasi Hubungan Arab Saudi dengan Qatar Tahun 2021 - Notodewo, Afif; Machmudi, Yon (Jurnal Ilmu Sosial Indonesia (JISI), 2022)
Abstract. Saudi Arabia and its ally, UAE (United Arab Emirates), Bahrain, and Egypt decided to end their diplomatic relations with Qatar and at the same time blockade Qatar through land, sea, and air in 2017. Saudi and its ally deemed that Qatar's relations and proximity with Iran and Turkey threaten their existence in the Gulf. But, there are political changes between Saudi and its ally with Qatar in 2021 which is marked by cooperation among them. This research will disclose the main reason why Saudi and Qatar decided to normalize their relationship which there are diplomatic changes in both states. This research uses grand theory neorealism and its middle theory relative gain and prisoner’s dilemma as analytical tools. As the result, there is a struggle for hegemony and geopolitical between Saudi Arabia, Iran, and Turkey in the Middle East and add with political change in the United States of America in which Joe Biden come to power and the spreading of Covid 19.Keywords: Saudi Arabia, Qatar, Neorealism, Relative Gain, Prisoner’s Dilemma. Abstrak. Arab Saudi beserta aliansinya, yaitu UEA (Uni Emirat Arab), Bahrain, dan Mesir memutuskan hubungan diplomatik dengan Qatar serta melakukan blokade jalur darat, air, dan udara pada 2017. Saudi dan aliansinya menganggap kedekatan Qatar dengan Iran dan Turki yang mengancam eksistensi mereka di kawasan Teluk. Namun, pada 2021 dunia dikagetkan dengan normalisasi hubungan antara kedua belah pihak ditandai dengan kerjasama. Penelitian ini membahas alasan mengapa Saudi dan Qatar melakukan normalisasi hubungan? Penelitian ini menggunakan kacamata grand theory neorealisme beserta teori relative gain dan prisoner’s dilemma. Hasilnya ditemukan bahwa terdapat perebutan hegemoni antara Saudi, Iran, dan Turki. Serta kondisi yang tidak menguntungkan Saudi seperti terpilihnya Joe Biden dan merebaknya pandemi Covid 19. Kata Kunci: Arab Saudi, Qatar, Neorealisme, Relative Gain, Prisoner’s dilemma.